2020
DOI: 10.1021/acs.chemmater.0c02798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Al Precursors on Deposition Selectivity of Atomic Layer Deposition of Al2O3 Using Ethanethiol Inhibitor

Abstract: Area-selective atomic layer deposition (AS-ALD) is a promising bottom-up patterning approach for fabricating conformal thin films. One of the current challenges with respect to AS-ALD is the deficiency of the surface inhibitor used for fabricating nanoscale three-dimensional structures. In this study, a vapor-deliverable small inhibitor called ethanethiol (ET) that thermally adsorbs on surfaces was used for the AS-ALD of Al2O3. The inhibitor selectively adsorbed on Co and Cu substrates but not on the SiO2 subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 40 publications
5
64
0
Order By: Relevance
“…The calculated value for Al(CH 3 ) 3 (76.8 kJ/mol) is similar to those of previously reported dimer dissociation energies (76.5−84.5 kJ/mol) for this species. 56,57 Compared to that of Al(C y H 2y+1 ) 3 , the dissociations of the AlCl 3 and Al(CH 3 ) 2 Cl precursors are less favorable, which is attributed to a strong Lewis acid−base interaction of the Al center and the Cl ligand in the Cl-containing precursors. Additionally, Al(C 2 H 5 ) 3 shows a similarly favorable dissociation energy to Al(CH 3 ) 3 , indicative that the strength of the dimer is related to the stability of the Al−X−Al bond (X = Cl for AlCl 3 and Al(CH 3 ) 2 Cl or C for Al(CH 3 ) 3 and Al(C 2 H 5 ) 3 ).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The calculated value for Al(CH 3 ) 3 (76.8 kJ/mol) is similar to those of previously reported dimer dissociation energies (76.5−84.5 kJ/mol) for this species. 56,57 Compared to that of Al(C y H 2y+1 ) 3 , the dissociations of the AlCl 3 and Al(CH 3 ) 2 Cl precursors are less favorable, which is attributed to a strong Lewis acid−base interaction of the Al center and the Cl ligand in the Cl-containing precursors. Additionally, Al(C 2 H 5 ) 3 shows a similarly favorable dissociation energy to Al(CH 3 ) 3 , indicative that the strength of the dimer is related to the stability of the Al−X−Al bond (X = Cl for AlCl 3 and Al(CH 3 ) 2 Cl or C for Al(CH 3 ) 3 and Al(C 2 H 5 ) 3 ).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The adsorption ratios of both precursors were simulated using a modified algorithm , running on simulation program “R” (version 3.6.1; GUI 1.70; El Capitan build 7684). The SiO 2 substrate was simulated as a single crystalline surface showing a 6-fold ring matrix.…”
Section: Methodsmentioning
confidence: 99%
“… 31 In addition, Kim et al reported area-selective Al 2 O 3 ALD on SiO 2 exploiting the selective adsorption of ethanethiol on Co and Cu. 32 Studies by Khan et al and Soethoudt et al have also shown that ALD precursors with inherent selectivity for precursor adsorption can be employed as SMI to achieve area-selective ALD. 36 , 37 …”
Section: Introductionmentioning
confidence: 99%